Comparison of Lattice Boltzmann, Finite Element and Volume of Fluid Multicomponent Methods for Microfluidic Flow Problems and the Jetting of Microdroplets (Communications in Computational Physics, 2023)
We show that the lattice Boltzmann method (LBM) based color-gradientmodel with a central moments formulation (CG-CM) is capable of accurately simulating the droplet-on-demand inkjetting process on a micrometer length scale by comparing it to the Arbitrary Lagrangian Eulerian Finite Element Method (ALE-FEM). Afull jetting cycle is simulated using both CG-CM and ALE-FEM and results are quantitatively compared by measuring the ejected ink velocity, volume and contraction rate.We also show that the individual relevant physical phenomena are accurately capturedby considering three test-cases; droplet oscillation, ligament contraction and capillaryrise. The first two cases test accuracy for a dynamic system where surface tension isthe driving force and the third case is designed to test wetting boundary conditions.For the first two cases we also compare the CG-CM and ALE-FEM results to Volumeof Fluid (VOF) simulations. Comparison of the three methods shows close agreementwhen compared to each other and analytical solutions, where available. Finally we demonstrate that asymmetric jetting is achievable using 3D CG-CM simulations utilizing asymmetric wetting conditions inside the jet-nozzle. This allows for systematicinvestigation into the physics of asymmetric jetting, e.g. due to jet-nozzle manufacturing imperfections or due to other disturbances.